MiR‐148a promotes myocardial differentiation of human bone mesenchymal stromal cells via DNA methyltransferase 1 (DNMT1). (3rd June 2018) - Jiang, Changke; Gong, Fang
Abstract: MicroRNAs have potential to modulate the differentiation of stem cells. In previous study, we found that miR‐148a was up‐regulated in myocardial differentiation of human bone mesenchymal stromal cells (hBMSCs) induced by 5′‐azacytidine. However, the role of miR‐148a in regulating this process still remains unclear. In this study, we investigated the function and molecular mechanism of miR‐148a in myocardial differentiation of hBMSCs. We found that miR‐148a was significantly increased while DNA methyltransferase 1 (DNMT1) was significantly decreased in myocardial differentiation of hBMSCs. Then, the dual luciferase reporter assays method indicated that DNMT1 was the direct target of miR‐148a. In addition, we showed that up‐regulation of miR‐148a could enhance myocardial differentiation of hBMSCs, while down‐regulation of miR‐148a could inhibit myocardial differentiation process. Moreover, knockdown of DNMT1 could block the role of miR‐148a in promoting myocardial differentiation of hBMSCs. Finally, MiR‐148a acted on methylation level of GATA‐4 and knockdown of DNMT1 could block this function. Therefore, our results indicate that miR‐148a plays a vital role in regulating myocardial differentiation of hBMSCs by targeting DNMT1.